Benefits of Recycling Plastic Bottles in Making Cleaning Materials at Bestlink College of the Philippines (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The research focused on how students’ learning benefits of an efficient broom to the students in terms of recycling plastic bottles. The study was revealed the aspects that may lead to the students’ behavior regarding the cleanliness of their classroom. Nowadays, the current problem about the cleanliness of classrooms has been increasing gradually. The students face many troubles because of the dirt inside the classroom that can cause disruption. Lack of cleanliness can be a major distraction to students that may affect their performance. A dirty classroom can also negatively affect health, attendance, and concentration. A clean school makes for a less stressful working environment. The classroom can be defined as an environment. Environmental pollutants include dirt, airborne, microbes, chemical vapors, and aerosol particles that students may be taken by students, which can result in some diseases. A qualitative method was used in this study by using a descriptive research design. This study involved 50 selected Grade 12 Accountancy, Business, and Management Strand students. Three variables were considered as benefits of plastic bottle brooms, including student’s learning and school management. A student’s learning is one of the factors that benefit students. Another aspect revealed that students may also enhance their creative thinking inside the classroom. The study revealed that a student’s learning has a benefit when they use recycled plastic bottle brooms during a discussion in classes. The study also showed that students reduced the amount of waste in their environment that will improve parental involvement.
Keywords: plastic bottle broomstick, student’s learning, school management